Implementation of Experimental Text Writing Learning in Internet Networks during the Covid-19 Period: A Case Study in Class IX of SMP Negeri 1 Kedung - Mohammad Khaizar Rohman; Andayani Andayani; Suyitno Suyitno (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
The purpose of this study is to describe: 1) planning for learning to write experimental texts through the internet during the COVID-19 period; 2) implementation of learning to write experimental texts through the internet; 3) obstacles in learning to write experimental texts through the internet; 4) solutions to overcome obstacles in learning to write experimental texts through the internet. This research is a qualitative research case study method with a qualitative descriptive approach. Sources of research data are: 1) informants include Indonesian language teachers and grade IX students; 2) documents include lesson plans, media, and learning materials. The sampling technique used the purposive sampling technique. Data collection techniques used are 1) interviews and 2) document analysis. The data analysis technique used is an interactive model. The results of this study were: 1) the planning of learning to write experimental texts through the internet network in class IX went well; 2) the implementation of learning to write experimental texts through the internet is well implemented; 3) The obstacles encountered are as follows: a) students are not used to or have not adapted to learning through the internet; b) the interest and motivation of students who are not used to doing learning through the internet are low; c) different levels of ability and interest among students; d) the teacher finds it difficult to give examples. 4) Solutions from the teacher are: a) the teacher motivates students to be active; b) the teacher gives continuous assignments; c) conduct two-way interaction; d) teachers collaborate with teaching materials with appropriate learning media. Furthermore, the solutions from the students are: a) students actively seek to ask questions and discuss; b) students try to adapt; c) students try to learn independently; d) students always try to learn the material given by the teacher.